Annual incidence and prevalence of injuries in elite male academy cricketers: A 4-year prospective cohort study - Williams, A.; Peirce, N.; Griffin, S.; Langley, B.; McKay, C.; Stokes, K. A.; Williams, S. (Journal of Science and Medicine in Sport Plus, 2024)
Objectives The aim of this study was to describe the epidemiology of injuries; time-loss and non-time loss, in elite male academy cricket.